Poultry Production Management on the Buildup of Nutrients in Litter - Watts , Dexter B.; Torbert, H. Allen; Codling, Eton E. (International Journal of Poultry Science, 2019)
Background and Objectives: It is believed that the poultry litter’s nutrient composition is influenced by management. However, limited information exists on whether current poultry litter management strategies influence litter nutrients. To fill this knowledge gap, Alabama poultry producers were surveyed to evaluate their management strategies and asked to submit a litter sample to determine how their production practices impacts poultry litter and its nutrient composition. Specifically, this study assessed the frequency of cleanout, the depth of sampling, the size of birds reared and the number of flocks raised on the bedding to determine how it influenced macro and micro nutrient concentrations of the litter. Materials and Methods: The influence of poultry rearing facility (broiler, breeder, or pullet) and whether the litter was collected from a poultry house, composter or dry stack barn was also evaluated. A total of 188 L samples submitted by producers were used for this study. Results: Averaging across all samples collected, the litter on an as-is basis had a fertilizer grade close to that of 3-3-2 for N, P2O5 and K2O, respectively. Litter collected from broiler production facilities had the highest overall macro- and micronutrient concentrations, while litter from composters had slightly higher N, P and Ca and lower C than litter taken directly from houses or drystack barns. The depth sampled, frequency of cleanout and number of flocks on the litter also influenced nutrient composition. Nutrients tended to be higher in caked litter than from sampling the entire six-inch depth. Litter nutrients tended to increase with flocks and decrease with frequency of cleanout. Conclusion: This study shows that differences in management may influence litter nutrient concentrations.